2006
DOI: 10.1111/j.1743-6109.2006.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Vulvar Vestibulitis Syndrome: Outcome Assessment Derived from a Postoperative Questionnaire

Abstract: Introduction Vulvar vestibulitis syndrome (VVS) is the most common pathology in women with sexual pain. Surgery for VVS was first described in 1981. Despite apparently high surgical success rates, most review articles suggest that surgery should be used only “as a last resort.” Risks of complications such as bleeding, scarring, and recurrence of symptoms are often used to justify these cautionary statements. However, there are little data in the peer-reviewed literature to justify this cautio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…18,[26][27][28]52,53,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] There was insufficient evidence to describe the size of the effect with certainty, due to risk of bias inherent in pain intervention studies without placebo controls. Case series of 1138 patients and randomized trials of 118 patients reported an effect of 31% to 100%, with a median of 79% for patients who reported at least some improvement to complete relief.…”
Section: Vestibulodynia Results: Surgical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[26][27][28]52,53,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] There was insufficient evidence to describe the size of the effect with certainty, due to risk of bias inherent in pain intervention studies without placebo controls. Case series of 1138 patients and randomized trials of 118 patients reported an effect of 31% to 100%, with a median of 79% for patients who reported at least some improvement to complete relief.…”
Section: Vestibulodynia Results: Surgical Interventionsmentioning
confidence: 99%
“…For 12 studies reporting complete relief as an outcome, the median effect size was 67%. 26,28,64,[66][67][68][69]71,72,[74][75][76] The absolute effect was estimated to be 30% from 1 randomized controlled trial (RCT). 27 The effect size from this single RCT could be consistent with the effect size seen with case series, on the basis that surgery has been reported to have a placebo effect of 35%, [79][80][81] and the placebo effect seen with vestibulodynia in RCTs of nonsurgical interventions was 40% to 50%.…”
Section: Vestibulodynia Results: Surgical Interventionsmentioning
confidence: 99%
“…Current treatment modalities include topical, oral and, injectable medications, physical therapy, dietary modifications, and surgery. 2,4 Sacral neuromodulation, or InterStim (Medtronic Inc., Minneapolis, MN), is a technology based on the surgical implantation of a device that allows chronic electrical stimulation of the sacral nerves using a battery-powered pulse generator. Sacral neuromodulation has been approved by the U.S. Food and Drug Administration for the treatment of urinary retention and the symptoms of overactive bladder, including urinary urge incontinence and urinary urgency or frequency or both in patients who have failed or could not tolerate more conservative treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative approaches have been suggested to improve the outcomes and recovery time for vestibulectomy; modified vestibulectomy, for example, involves the excision of tissue only at the posterior vestibule [85]. Over the past 2 decades, retrospective [84,[86][87][88][89][90][91][92] and prospective [85,[93][94][95][96][97] studies have reported similar success rates for surgical interventions, ranging from 49 to 94%. However, differences in surgical procedures, measurement and operationalization of successful outcomes, as well as variable follow-up rates limit comparison across studies.…”
Section: Medical Treatments Surgerymentioning
confidence: 94%
“…Vestibulectomy, the removal of this tissue, has the highest success rates of the current treatments for PVD [83], and although surgical intervention is typically not recommended before less invasive treatment options have been explored [82,83], it may be offered as a first-line treatment for PVD in some instances [84]. The surgery most commonly involves the excision of posterior and anterior vestibular tissue, and of the posterior hymen to a depth of a few millimeters [83].…”
Section: Medical Treatments Surgerymentioning
confidence: 99%